Species-area curves based on releve data for the Cape Floristic Region - Mucina, Ladislav; Proches, S.; Cowling, Richard (2003)
Relevé data were used to compare species–area curves for the western and eastern parts of the Cape Floristic Region (CFR). Observed differences related more often to vegetation heterogeneity than to the geographical position of the localities. However, when separating plant species according to their distribution ranges, CFR endemics contributed greatly to diversity values in the west. CFR non-endemics, on the other hand, boosted species richness in the east, many of them appearing as 'pseudorares', owing to the greater diversity of vegetation types, which include formations with marginal intrusion into the CFR.